Effects of an exercise program during pediatric stem cell transplantation: A randomized controlled trial. Issue 5 (23rd February 2022) - Smith, Charles; Farhat, Ryan; Fern‐Buneo, Anna; Purrington, Heidi; Cobb, Ellie; Matson, Laura; Kang, Paul; Beebe, Kristen; Campbell, Courtney; Schwalbach, Charlotte; Salzberg, Dana; Miller, Holly; et al.
Abstract: Background: During pediatric hematopoietic stem cell transplant (HSCT), there is significant reduction in physical activity, leading to loss of strength and function, along with decline in quality of life (QoL). This study evaluates the effects of a supervised exercise program on functional ability, mobility, strength, and QoL during and following pediatric HSCT. Methods: Patients ages 4–21 years presenting for HSCT were randomized to either an intervention group, who underwent exercise routines three times weekly and once weekly on discharge for 6 weeks supervised by a physical therapist, or the control group, which was treated per standard of care. Forty subjects were recruited for the study, 20 in each arm. Physical therapy and QoL assessments were conducted at three time points: pre‐HSCT (baseline), on the day of hospital discharge, and 6 weeks after discharge. Results: Exercise capacity and endurance using Six‐Minute Walk test ( p  = .023) and strength using manual muscle testing ( p  = .005) were improved in the exercise group, compared to the control group. There was evidence that some QoL outcomes (measured using the Patient Reported Outcomes Measurement Information System) were improved 6 weeks post discharge, with observed decreases in anxiety ( p  = .0009) and fatigue ( p  = .037). Conclusion: Supervised exercise program during pediatric HSCT has positive effects on endurance, functional mobility, and muscle strength, and may also result in improvements in some aspects of QoL. This trial was registered at www.clinicaltrials.gov as NCT04663503.